Effect of heat treatment on structural properties of silica borotellurite glasses containing MnO - Ismail, Zaitizila; Mohamed Kamari, Halimah; Muhammad, Farah Diana; Mohd Shah, Nurisya (IOP Publishing, 2018)
{[(TeO2)0.7(B2O3)0.3]0.8[SiO2]0.2}1-xMnO2x where x = 0.00, 0.01, 0.02, 0.03, 0.04 and 0.05 molar fraction were prepared by using melt quenching technique. Heat treatment of the glass sample was performed at 600 °C for 3 hours. The structure of the glass samples was characterized by using Fourier Transform Infrared (FTIR) and X-ray diffraction (XRD). Crystalline phase was recorded after parent glass went through heat treatment process. The FTIR spectra for parent glass and heat treated glass samples validate the presence of TeO4, TeO3, BO4, BO3 and Si-O(Si) in the glass network. After the samples were heat treated, vibration from manganese group were detected in FTIR spectra.